Integrating Islamic Values and Digital Technologies in Islamic Educational Management: A Contemporary Framework - Musyarofatus Sania Putri Wardoyo (Al-Qalam Institue, 2025)
This study aims to examine how Islamic values can be integrated with the use of digital technologies in the management of Islamic educational institutions. Employing a qualitative library research approach, the study reviews scholarly books, indexed journal articles, conference proceedings, and research reports relevant to value-based educational management and technological innovation. The analysis focuses on key ethical principles, including amanah, justice, consultation, and ihsān. It explores how these principles interact with digital tools, including academic information systems, online learning platforms, and school management applications. The findings indicate that technology can significantly enhance managerial effectiveness when its utilization is guided by Islamic values that emphasise moral accountability and responsible governance. However, the study also identifies persistent challenges, particularly in digital literacy, human resource readiness, and the need for ethically grounded regulations. These findings underscore the need to maintain a balanced approach that aligns technological innovation with Islamic ethical integrity. The study contributes to value-driven management discourse and offers practical implications for strengthening digital transformation in Islamic educational institutions.